Caracterização de painéis de partículas de madeira tratada com CCB confeccionados com resina poliuretana mista - Shirosaki, Rodrigo Kiyoshi (Universidade Federal de São Carlos, 2019)
The particleboard is an engineered product of the wood, made from the gluing of small, deconstructed pieces from the wood processing using a bonding resin. Because it is a material subject to attack by xylophagous organisms, the wood treatment with preservative is essential to ensure its durability. The CCB (chromium, copper and boron salts) is a more interesting alternative to CCA (chromium, copper and arsenic salts) due to its efficiency in combating degradation and, especially, lower toxicity. The mixed polyurethane resin based on vegetable oils is also a choice over traditional urea-based resin, whose major problem is the emission of formaldehyde during pressing. The wood of the genus Pinus has low density and accepts well the preservative treatment due to the greater porosity when compared with hard wood. It is also the second most planted genus in Brazil, only behind Eucalyptus. Therefore, this study aims to analyze the technical feasibility of particle board production using Pinus wood treated with CCB and polyurethane resin based on vegetable oils. For this, three different resin concentrations (10%, 12% and 15%) were used in combination with the presence or absence of the preservative, obtaining 6 types of treatment. The results met the normative requirements of Brazilian documents ABNT NBR 14810 (2013) and European EN 312 (2003), in addition to reaching values close to and even higher than similar surveys. Therefore the technical feasibility of making panels with said materials used and the quality of the product according to its excellent performance were verified.
Characterization of panels of wood particles treated with CCB made with mixed polyurethane resin
Keywords: Madeira; Pinus; Painel de partículas; CCB; Resina poliuretana; Wood; Particle board; Polyurethane resin; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS